2017
DOI: 10.1515/amm-2017-0268
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Process Parameters in Drilling LM25 Composites Coated with Multi Wall Carbon Nano Tubes Using Sonication Process

Abstract: Aluminium based metal matrix composites are widely used in automobile components such as cardan shaft of Chevrolet corvette, disc brake and engine push rod. In this experiment a Hybrid Metal Matrix Composites (HMMC) are fabricated and drilled. Drilling is the process of making slots in disc brake and thread in the engine parts. The surface quality of the drilled specimen depends on the speed, feed, drill type and the thrust force. Thrust force plays the major role in drilling the specimen. In this experiment H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Thrust force is measured using dynamometer in a vertical machining center in a graphical form. It is revealed that the thrust force is minimum at the entry and exit of tool, and it is maximum during the drilling process [25]. Figures 3(a) and 3(b) show the mean and signal-to-noise ratio, and they are opposite to each other.…”
Section: Analysis Of Thrust Forcementioning
confidence: 93%
“…Thrust force is measured using dynamometer in a vertical machining center in a graphical form. It is revealed that the thrust force is minimum at the entry and exit of tool, and it is maximum during the drilling process [25]. Figures 3(a) and 3(b) show the mean and signal-to-noise ratio, and they are opposite to each other.…”
Section: Analysis Of Thrust Forcementioning
confidence: 93%